Pengaruh Profesionalisme dan Aspek Kepribadian Pada Analisis Efektivitas Pemberian Kredit di Bank Negara Indonesia Denpasar - Puspitayani, Ni Kadek Nandya; Suartana, I Wayan (E-Jurnal Akuntansi; Vol 24 No 2 (2018)DO - 10.24843/EJA.2018.v24.i02.p01, 2018)
This study aims to obtain empirical evidence on the effect of Professionalism, Machiavellian nature, and Organizational Commitment to the analysis of credit effectiveness. This research was conducted at PT. Bank Negara Indonesia (PERSERO), Tbk Denpasar Area. The number of samples used were 31 people using non probability sampling with saturated sampling approach. Data collection method was conducted by survey method using questionnaire. Data analysis technique used is multiple linear regression analysis. Based on the results of research, it is known that professionalism has a positive effect on the analysis of credit effectiveness. The Machiavellian nature negatively affects the analysis of credit effectiveness, whereas organizational commitment has a positive effect on credit effectiveness analysis. Keywords: Profesionalism, Machiavellian Characteristics, Organizational Commitment, and Credit Effectiveness Analysis